Analisis Pengaruh Endorsement dan Ulasan Pelanggan Online Terhadap Loyalitas Merek di Mediasi Oleh Sikap Pelanggan - Purwaningsih, Putri Mulya (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
This study aims to analyze the influence of endorsements and online customer reviews on brand loyalty, with customer attitudes as a mediating variable. This study was conducted on Wardah Beauty consumers in Sukabumi City using a quantitative approach using Structural Equation Modeling (SEM). A total of 140 respondents were used. The results show that both endorsements and online customer reviews have a positive and significant effect on customer attitudes. Furthermore, both variables also have a direct effect on brand loyalty. Customer attitudes were also shown to significantly influence brand loyalty and mediate the relationship between the independent variables and loyalty. These findings provide theoretical and managerial implications regarding the importance of building positive perceptions through public figures and customer testimonials in digital marketing strategies.